ENGARUH PEMBERIAN INSENTIF DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA BAGIAN PEMASARAN DI PT. TUNAS DWIPA MATRA PEKANBARU - Wibowo, Yollanda Salsabillah; Nuryanti, Nuryanti; Ningsih, Dewita Suryati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
his study aims to determine the effect of providing incentives and motivation on employee performance with job satisfaction as an intervening variable in the marketing department of PT.  Tunas Dwipa Matra Pekanbaru. The population in this study included 40 marketing employees.   The primary data collected with a questionnaire as an instrument to prove the results of the research, to test the hypothesis in this study is Structural Equation Modeling-Partial Least Square (SEM-PLS) data analysis, which was operated through the SMART/PLS program.  The selected sampling technique is the census method (40 employees of the marketing division of PT. Tunas Dwipa Matra Pekanbaru.  The results showed that: 1) There is a significant influence between incentives on job satisfaction in the marketing department at PT.  Tunas Dwipa Matra Pekanbaru, 2) There is a significant influence between motivation on job satisfaction in the marketing department at PT.  Tunas Dwipa Matra Pekanbaru 3) There is a significant influence between incentives on employee performance in the marketing department at PT.  Tunas Dwipa Matra Pekanbaru, 4) There is a significant influence between motivation on employee performance in the marketing department at PT.  Tunas Dwipa Matra Pekanbaru 5) There is a significant influence between job satisfaction on employee performance in the marketing department at PT.  Tunas Dwipa Matra Pekanbaru, 6) There is a significant influence between incentives on employee performance in the marketing department of PT.  Tunas Dwipa Matra Pekanbaru, 7) There is a significant influence between motivation on employee performance in the marketing department at PT. Tunas Dwipa Matra Pekanbaru, Keywords: Incentives, Motivation, Employee Performance, Job Satisfaction.